Photocatalyst‐Free and Blue Light‐Induced RAFT Polymerization of Vinyl Acetate at Ambient Temperature. Issue 24 (7th October 2015) - Ding, Chunlai; Fan, Caiwei; Jiang, Ganquan; Pan, Xiangqiang; Zhang, Zhengbiao; Zhu, Jian; Zhu, Xiulin
Abstract : Vinyl acetate is polymerized in the living way under the irradiation of blue light‐emitting diodes (LEDs) or sunlight without photocatalyst at ambient temperature. 2‐(Ethoxycarbonothioyl)sulfanyl propanoate is exclusively added and acts as initiator and chain transfer agent simultaneously in the current system. Poly(vinyl acetate) with well‐regulated molecular weight and narrow molecular weight distribution ( Đ < 1.30) is synthesized. Near quantitative end group fidelity of polymer is demonstrated by nuclear magnetic resonance (NMR) and matrix‐assisteed laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS). Abstract : This visible‐light LED‐induced living radical polymerization of vinyl acetate offers an easy way to synthesize pure polymer with predetermined structure. Xanthates directly initiate living radical polymerization of vinyl acetate under the irradiation of blue LED. This method offers an easy way to synthesize pure poly(vinyl acetate) with predetermined structure, especially for various terminal functionalized structures with high fidelity.